The ant genus Tetramorium Mayr (Hymenoptera: Formicidae) in the Malagasy region—taxonomy of the T. bessonii, T. bonibony, T. dysalum, T. marginatum, T. tsingy, and T. weitzeckeri species groups - Garcia, Francisco Hita; Fisher, Brian L. (Zootaxa, 2012)
The taxonomy of the T. bessonii, T. bonibony, T. dysalum, T. marginatum, T. tsingy, and T. weitzeckeri species groups isrevised. A total of 33 species is treated, of which 27 are newly described and one is raised to species status. The T.weitzeckeri group contains the single species T. humbloti Forel, which is of Afrotropical origin and the only representativeof the group in the Malagasy region. The species T. bessonii Forel, T. dysalum Bolton, T. marginatum Forel, and T. stein-heili Forel, which were originally members of the T. weitzeckeri group, are now placed in other groups. Tetramorium bes-sonii is the core species of the T. bessonii group, which also contains the four newly described species T. artemis sp. n., T.malagasy sp. n., T. ryanphelanae sp. n., T. wardi sp. n., and T. orientale Forel stat. n., which was a junior synonym of T.bessonii but is now raised to species rank. The T. dysalum group is a moderately-sized group with ten species, of whichonly T. dysalum and T. steinheili were previously known; the other eight species are all newly described. The newly described species in this group are: T. ambatovy sp. n., T. macki sp. n., T. mallenseana sp. n., T. orc sp. n., T. robitika sp. n.,T. sargina sp. n., T. yammer sp. n., and T. vohitra sp. n. A lectotype and several paralectotypes of T. steinheili are desig-nated. Tetramorium marginatum is the central species of the T. marginatum group, which also includes the five newly de-scribed species T. valky sp. n., T. hector sp. n., T. norvigi sp. n., T. shamshir sp. n., and T. silvicola sp. n. The T. bonibonyand T. tsingy groups represent completely new groups that consist entirely of previously unknown, undescribed species.The first group holds the new species T. bonibony sp. n., T. kali sp. n., T. sada sp. n., T. nosybe sp. n., T. olana sp. n., T.popell sp. n., and T. trafo sp. n. and T. vony sp. n. The last group, the T. tsingy group, only contains the two species T. tyrionsp. n. and T. tsingy sp. n., both among the rarest Tetramorium species in Madagascar. All groups are fully revised withillustrated species-level identification keys, and all species are described/re-described and illustrated with high qualitymontage images. In addition, the current status of the Malagasy Tetramorium species groups is discussed and further modifications are proposed.